DOP48 Amiselimod, a selective S1P receptor modulator in Crohn's disease patients: a proof-of-concept study. (25th January 2019) - D'Haens, G; Danese, S; Davies, M; Watanabe, M; Hibi, T
Abstract: Background: The treatment of Crohn's disease (CD) remains unsatisfactory for many patients leading to poor quality of life and surgery. Amiselimod (AMS) is a new selective oral S1P receptor modulator, which is being developed for the treatment of various autoimmune-mediated disease including CD. Methods: This was a prospective, randomised, placebo (PLC) controlled clinical trial in which patients with active CD (CDAI 220-450) and elevated biomarkers received 0.4 mg of AMS or PLC for 14 weeks, followed by open-label extension treatment. Patients had to have been previously treated with corticosteroids or immunosuppressants and/or anti-TNF-α agents for CD. The primary endpoint was clinical response defined as drop in the CDAI by 100 points at Week 12 (CDAI100). Results: One hundred and eighty patients underwent screening and 78 (median age 33, 61.8% male, median baseline CDAI 307, 60.5% anti-TNF exposed) were randomised (40 to AMS and 38 to PLC). Baseline characteristics were similar among groups. Twenty-eight of 40 patients on AMS and 33/38 on PLC completed the induction trial. The primary endpoint CDAI100 was attained in 19/39 (48.7%) on AMS vs. in 20/37 (54.1%) on PLC (NS). CDAI 70 and clinical remission (CDAI<150) were observed in 21/39 (53.8%) and 11/39 (28.2%) on AMS and in 24/37 (64.9%) and 15/37 (40.5%) on PLC, respectively. No clinically meaningful differences were observed in serum CRP concentrations and faecal calprotectin in either groups. Mean lymphocyte counts on AMS showed significant reduction by Week 4 (47.7% of baseline), after which, mean lymphocyte counts reached graphical plateau. This lymphocyte counts reduction was considered weaker than the other indications and simulated data from MT-1303 Phase I studies. TEAEs were observed in 66.7% of patients on AMS and in 55.3% on PLC with infections occurring in twice as many patients on AMS than in PLC (26 vs. 13%). Cardiac disorders were reported in 3 patients on AMS (TEAEs: ventricular tachycardia, bradycardia, supraventricular extrasystoles, and ventricular extrasystoles) and in 1 on PLC (ventricular tachycardia). They were all mild and considered non-serious. There were no clinically relevant findings between AMS and PLC in the mean hourly HR, and no clinically significant reports of bradycardia, AV block and ventricular tachycardia. Macular oedema was confirmed in 1 patient on AMS (mild and considered non-serious). Conclusions: Treatment with AMS 0.4 mg was generally well tolerated and no new safety concerns related to AMS were reported in this study. AMS 0.4 mg/day for 12 weeks did not have an effect on clinical or biochemical disease activity in refractory CD, and the high placebo response rate and weaker lymphocyte reduction were considered to contribute to the negative efficacy result in this study.